Human biomonitoring of neonicotinoid exposures: case studies after the use of a spray-agent to ornamental plants and a topical medication to pets - Sonja A. Wrobel; Stephan Koslitz; Daniel Bury; Heiko Hayen; Holger M. Koch; Thomas Brüning; Heiko U. Käfferlein (Frontiers Media S.A., 2024)
Acetamiprid (ACE) and imidacloprid (IMI) are insecticides of global importance and are used as spray and watering agents for ornamental plants to control biting and sucking insects or as topical medications on pets to remove and control fleas. Human biomonitoring data on ACE and IMI exposures when applying these products are limited. We investigated exposures to ACE and IMI in male volunteers after the domestic application of either an ACE-containing agent or an IMI-containing spot-on medication. Complete and consecutive urine samples were collected for up to 56 h after application. Urine samples were analyzed for ACE, IMI, and their respective metabolites (N-desmethyl-ACE, IMI-olefin, and sum of 4−/5-hydroxy-IMI) by liquid chromatography-tandem mass spectrometry. Fairly uniform concentrations of N-desmethyl-ACE could be observed before and after orchid treatment, so that an ACE exposure associated with orchid treatment can most likely be excluded. In contrast, after the application of the IMI-containing medication, elevated concentrations of IMI, 4−/5-hydroxy-IMI, and IMI-olefin were quantified in urine samples post-20 h with maximum concentrations of 3.1, 14.9, and 8.0 μg/g creatinine, respectively, well above general background levels. Nevertheless, the IMI intake (10.6 μg/kg bw), calculated from the excreted amounts, was around five times below the current European acceptable daily intake. Based on the case results here, household exposures to ACE and IMI after spray treatment of ornamental plants and anti-flea treatment of dogs can be regarded as low and safe. However, people regularly applying neonicotinoid-containing formulations, such as professional gardeners and employees in animal shelters, should be studied in more detail.